The dark sides of amyloid in Alzheimer's disease pathogenesis. Issue 5 (31st January 2014) - Sorrentino, Pierpaolo; Iuliano, Antonietta; Polverino, Arianna; Jacini, Francesca; Sorrentino, Giuseppe
Abstract : Although widely explored, the pathogenesis of Alzheimer's disease (AD) has yet to be cleared. Over the past twenty years the so call amyloid cascade hypothesis represented the main research paradigm in AD pathogenesis. In spite of its large consensus, the proposed role of β‐amyloid (Aβ) remain to be elucidated. Many evidences are starting to cast doubt on Aβ as the primary causative factor in AD. For instance, Aβ is deposited in the brain following many different kinds of injury. Also, concentration of Aβ needed to induce toxicity in vitro are never reached in vivo . In this review we propose an amyloid‐independent interpretation of several AD pathogenic features, such as synaptic plasticity, endo‐lysosomal trafficking, cell cycle regulation and neuronal survival.